Synthesis of novel fused chromone–pyrimidine hybrids and 2, 4, 5-trisubstituted pyrimidine derivatives via ANRORC rearrangement. (15th August 2017) - Sambaiah, M.; Raghavulu, K.; Shiva Kumar, K.; Yennam, Satyanarayana; Behera, Manoranjan
Abstract : A facile and versatile procedure for the synthesis of functionalized novel 2, 5-diphenyl-5 H -chromeno[4, 3- d ]pyrimidin-5-ol and (2, 4-diphenylpyrimidin-5-yl) (2-hydroxyphenyl) methanone has been described. Abstract : A facile and versatile procedure for the synthesis of functionalized novel 2, 5-diphenyl-5 H -chromeno[4, 3- d ]pyrimidin-5-ol and (2, 4-diphenylpyrimidin-5-yl) (2-hydroxyphenyl) methanone has been described. The key step in the synthesis involves the ANRORC reaction of 3-benzoyl chromones with benzamidines.